Counseling Guidance Teacher Services in Increasing Student Learning Motivation from Broken Home Families - Felia Agriani (Penerbit Hellow Pustaka, 2023)
Counseling teacher services are a preventive effort so that students are not on the wrong path, students who have problems cannot solve their own problems, they need someone who can help in alleviating the problem. Especially in the case of broken home students in adolescents, where students are in a phase of searching for identity, and broken home students are different from other students, they have quite serious personal problems, one of which is loss of motivation to study. Based on the reality above, researchers are trying to explore the Service Counseling Guidance Teacher in Increasing Students' Learning Motivation Broken Home in Grade IX Students of SMP Negeri 1 Balongan. Thus, researchers can formulate problems that will be studied in the preparation of this research. First, how is the guidance and counseling teacher's service in increasing the learning motivation of broken home students? Second, how is the effectiveness of guidance and counseling teacher services in increasing the learning motivation of broken home students? The type of this research is field research using descriptive research methods with a qualitative approach. The research technique used is data collection techniques and data analysis techniques. Data collection techniques were carried out by means of observation, interviews and documentation. The results of this study are that the guidance and counseling teacher's service in increasing the learning motivation of broken home students in class IX has been going well, the service used by the counseling teacher in this case is group guidance, but in students with weak cases the motivation to study is quite serious so causing students to be reluctant to go to school, counseling teachers use home visit services. The services provided by the counseling teacher in increasing learning motivation in broken home students in class IX at SMP Negeri 1 Balongan can be said to be effective, because in the results of the interviews the students were satisfied with the services provided by the guidance and counseling teacher, as evidenced by positive responses and changes in themselves student